Analisis Aksesbilitas Fasilitas Kesehatan di Kota Pekanbaru, Indonesia - Eggy Arya Giofandi; Amira Novalinda; Dhanu Sekarjati; Muh. Anugrah Pratama; Cipta Estri Sekarrini (UNIVERSITAS PELITA HARAPAN, 2023)
Health services are one of the most important facilities and help improve the quality of life and social welfare of modern society. Recent advances in the field of health geography have greatly enhanced our understanding of the role that geography of health care distribution plays in the maintenance of population health. This study presents a two-stage methodology for evaluating the location of existing health facilities in Pekanbaru City and estimating the area of buildings that are not covered by health facilities. The results obtained during the study resulted in the finding that several facilities were close together so that the measurement results overlapped to form a wedge, while the estimated built-up land that was not covered by health facilities was 3,259 hectares. This condition is expected to be able to develop health facilities that will be useful in settlements on the outskirts of the city, this hopefully can be one of the initial conditions to determine the development of health locations in the next planning.